RNA interference mutant induction in vivo demonstrates the essential nature of trypanosome flagellar function during mammalian infection. - Griffiths, S; Portman, N; Taylor, P; Gordon, S; Ginger, M; Gull, K (2007)
We demonstrate that trypanosomes compromised in flagellar function are rapidly cleared from infected mice. Analysis of the PFR2 bloodstream RNA interference mutant revealed that defective cell motility occurred prior to cytokinesis failure. This validation provides a paradigm for the flagellum as a target for future assays and interventions against this human pathogen.